Effect of caffeine supplementation during treadmill exercise on hippocampal genes expression levels in adolescent rats - Bakır, Fatma; Çevik, Özge Selin; Müsüroğlu Keloğlan, Seval; Şahin, Leyla (The European Research Journal, 2023)
Objectives: The usage of caffeine, a psychostimulant that is included in many foods and drinks, is rising, especially among young people. Also, caffeine works as an ergogenic substance during exercise to improve performance, and strength. In this study, our aim was to investigate the effect of caffeine consumption and exercise on hippocampal learning and memory functions in early life. Methods: Postnatal 28 days old Wistar albino male rats (n = 28) were randomly divided into 4 groups; control group (C), caffeine group (Cf), exercise group (E), caffeine+exercise group (CfE). Caffeine was dissolved in drinking water (0.3 g/L) and the treadmill exercise was applied 3 days a week. Following, the rats were applied to Morris Water Maze Test (MWMT) and open field test. N-methyl-D-aspartate (NMDA) receptors NR2A, NR2B, and brain-derived neurotrophic factor (BDNF) gene expression levels were investigated in hippocampus tissue by RT-PCR. Results: In MWMT, there was no significant difference in terms of learning and memory functions and hippocampal gene expression levels of the groups (p > 0.05). In the open field test, the time spent in the center was decreased in the CfE group, and the number of entries to the center was decreased in the E and CfE groups compared to the control group (p < 0.05). Conclusions: We assumed that caffeine given with exercise application caused anxiety behavior but did not affect learning and memory. There is a need for new studies investigating the effect of caffeine on exercise with different doses and durations depending on age.